Temporary employment and its impact on wages in Latin America - Maurizio, Roxana (Iberoamerican Journal of Development Studies, 2019)
Latin America has experienced a process of significant improvement in the labour market during the new millennium. In spite of these advances, these countries continue to suffer from remarkable deficits in their labour markets. The high incidence of informality becomes a source of low wages and lack of social security benefits. Even within formal employment, the significant prevalence of non-permanent contracts frequently leads to consequences similar to those of informal occupations. This paper analyses fixed-term contracts in eight Latin American countries: Argentina, Brazil, Chile, Costa Rica, Ecuador, Mexico, Paraguay and Peru. We aim at estimating the incidence, evolution and characteristics of this phenomenon and assessing to what extent temporary employment generates wage gaps. Econometric techniques are used in order to estimate not only the average wage gap between these two groups of workers but also the penalty suffered by temporary workers located at different points of the wage distribution.